Peran Perguruan Tinggi dalam Menjaga Integritas Akademik pada Era Digital - Keysha Amelia; Gita Elizza Larasati; Vaskya Nabila Putri; Nur Aini Rakhmawati (Universitas Katolik Widya Karya Malang, 2024)
In the digital era, universities play an important role in developing policies and technology to ensure students' academic integrity. This research aims to explore and analyze holistically the contribution and effectiveness of universities in maintaining academic integrity in the digital era. The research method used is a literature review with a semi-systematic review approach, which is then expanded with bibliometric analysis using the VOSViewer tool. Of the 115 papers identified in the bibliometric analysis with the keyword “college plagiarism”, it was found that the term “plagiarism” was often associated with “student”, “college”, “academic”, and “plagiarism”. Key relevant terms include “training”, “locus of control”, “rabin-karp”, “text mining”, “hash”, “levenshtein distance algorithm”, “similarity”, and “publication”. Universities should conduct training and strengthen students' locus of control to instill integrity values. The concept of “similarity” in plagiarism detection helps maintain the originality of academic work, while “rabin-karp” and “text mining” technologies are used to recognize plagiarized text and find suspicious patterns. The “hash” concept and “Levenshtein distance algorithm” are important in maintaining academic integrity, and “publication” ensures research meets academic integrity standards. Universities leaders are responsible for preventing plagiarism by implementing code of ethics and promoting awareness and understanding within the entire academic community.